2010
DOI: 10.1016/j.cca.2010.05.021
|View full text |Cite
|
Sign up to set email alerts
|

CYP2C9 and VKORC1 genotypes in Puerto Ricans: A case for admixture-matching in clinical pharmacogenetic studies

Abstract: Backgrounds-Admixture is of great relevance to the clinical application of pharmacogenetics and personalized medicine, but unfortunately these studies have been scarce in Puerto Ricans. Besides, allele frequencies for clinically relevant genetic markers in warfarin response (i.e., CYP2C9 and VKORC1) have not yet been fully characterized in this population. Accordingly, this study is aimed at investigating whether a correlation between overall genetic similarity and CYP2C9 and/or VKORC1 genotypes could be estab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 34 publications
1
12
0
Order By: Relevance
“…8 Several single nucleotide polymorphisms (SNPs) in VKORC1 have been associated with a deficiency in vitamin-K dependent clotting factors, resulting in either increased sensitivity to w-arfarin or warfarin resistance. 9 Warfarin inhibits VKORC1 activity by reducing the regeneration of vitamin K and thus exerting its anticoagulation effect. 1,2,7 Reduced vitamin K is the essential cofactor for the activation of clotting factors II, VII, IX and X and proteins C, S and Z by g-glutamyl carboxylase, encoded by GGCX.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 Several single nucleotide polymorphisms (SNPs) in VKORC1 have been associated with a deficiency in vitamin-K dependent clotting factors, resulting in either increased sensitivity to w-arfarin or warfarin resistance. 9 Warfarin inhibits VKORC1 activity by reducing the regeneration of vitamin K and thus exerting its anticoagulation effect. 1,2,7 Reduced vitamin K is the essential cofactor for the activation of clotting factors II, VII, IX and X and proteins C, S and Z by g-glutamyl carboxylase, encoded by GGCX.…”
Section: Introductionmentioning
confidence: 99%
“…10 These alleles can cause alterations in initial warfarin dose sensitivities, delays in achieving a stable maintenance dose, and increased risk of serious or life-threatening bleeding complications. 9 Large body of previous studies on the inter-individual variability of warfarin have demonstrated that the genetic variations in the VKORC1 as well as CYP2C9, a warfarin metabolizing enzyme, influence warfarin responses. 3,4 Moreover, recently it has been revealed that a genetic variation of cytochrome P450 4F2 (CYP4F2) is also associated with a clinically relevant effect of warfarin.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, we searched for this information in the articles in our sample. Although the use of ethnicity as an indicator for genotype has been the subject of much criticism (e.g., Suarez-Kurtz et al, 2010;Villagra et al, 2010), it remains that in the context of nutrigenetics research, the notion of ethnicity can provide important information. Indeed, ethnicity may give some indications on the frequency of a given polymorphism, as is the case with lactose intolerance in Asian populations (Lomer et al, 2008).…”
Section: (V) Limitations Resulting From the Complexity Of The Geneticmentioning
confidence: 98%
“…[68]], but also within such populations or groups [e.g. [69,70]]. ‘Therefore, before appropriate genotyping panels can be established, the extent of functional genetic variation in candidate genes needs to be determined, especially in understudied populations’ [[71], p. 340].…”
Section: Discussionmentioning
confidence: 99%